Pelatihan dan Pengelolaan Website Desa Narawita Menuju Smart Village - Widianingsih, Ayang Winda Sri; Kulsum, Eva Meidi; Widya, Dede Widya; Aufanviga, Putra Aufanviga (Ma'soem University, 2025)
The objective of this Community Service Program is to enhance the Human Resources (HR) capacity of Village Officials in Bandung Regency in website management as a fundamental step towards implementing the Smart Village concept. The activity was motivated by a significant digital gap where village websites were often neglected, not up-to-date, and thus hindered the principle of transparency. This PkM activity was conducted from July 07, 2025, to August 18, 2025, in Narawita Village, Cicalengka District, Bandung Regency, involving representatives of Village Officials, including the Village Secretary and the village IT team. The method employed was Participatory Action Research, commencing with a Needs Analysis (FGD and Pre-Test), followed by the creation of a new website using Visual Studio Code, and cyclical Testing (Uji Coba) with consultation from village stakeholders. The core phase involved Intensive Training for transferring skills in basic web maintenance, digital content literacy, and promotional strategies. The results demonstrate a dual success: first, the creation of a stable and functional website (https://sistem-informasi-desa-narawita-blzu.vercel.app/) equipped with transparency and promotional modules; second, a significant increase in the competency of Village Officials in managing content independently, supported by continuous knowledge transfer. This success was consolidated by the development of a Website Management SOP, ensuring the project's sustainability and transforming local human resources. Overall, this Community Service successfully laid the foundation for Smart Governance and Smart Economy, asserting that intervention in HR capacity is the main key to realizing the Smart Village vision in Bandung Regency.